Kesantunan Berbahasa dalam Retorika Politik: Register Bahasa Mahyeldi dan Epyardi dalam Debat Publik Pemilihan Gubernur Provinsi Sumatera Barat pada Kanal Youtube KPU Sumbar - Yumelta Novita; Syofiani Syofiani; Hasnul Fikri (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Language variation in the political sphere gives rise to registers shaped by the speakers’ styles, which often neglect principles of politeness. This study aims to analyze the politeness strategies employed by Mahyeldi and Epyardi Asda in the 2024 West Sumatra Gubernatorial Public Debate based on Geoffrey Leech’s (1983) Politeness Principle and the concept of kato nan ampek (Navis, 1986). This research adopts a qualitative approach using pragmatic discourse analysis. The data consist of transcriptions of both candidates’ utterances, which were examined according to Leech’s six politeness maxims and the values of kato nan ampek. Data collection techniques included observation, transcription, note-taking, data classification, documentation, and data inventory. The data were analyzed through reduction, data presentation, contextual analysis, and conclusion drawing. The findings reveal that out of 37 analyzed utterances, only 9 complied with Geoffrey Leech’s politeness principles, while 28 violated them. Compliance was predominantly demonstrated by Mahyeldi, particularly in the tact maxim, whereas Epyardi Asda showed no compliance and more frequently violated the agreement, tact, and modesty maxims. Based on the kato nan ampek framework, Mahyeldi tended to use polite forms in kato mandaki and kato malereang, while Epyardi Asda more frequently violated kato mandaki through derogatory insinuations. These differences have implications for the construction of public image and societal perception, indicating that linguistic politeness plays a significant role in political communication.